2020
DOI: 10.1177/1940161220959553
|View full text |Cite
|
Sign up to set email alerts
|

Images, Politicians, and Social Media: Patterns and Effects of Politicians’ Image-Based Political Communication Strategies on Social Media

Abstract: Although images have always been part of politics, research on the visual aspects of political communication recently gained momentum, especially with the spread of social media–based political communication. However, there are still several significant research gaps in this field. The aim of this article is to identify and compare the patterns and effects of Hungarian politicians’ ( n = 51) image-based communication on Facebook ( n = 2,992) and Instagram ( n = 868) during the Hungarian parliamentary election … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 33 publications
1
45
0
17
Order By: Relevance
“…This also means that we cannot assess what the engagement with EU news, as operationalized in this study, might mean in terms of legitimacy or support for the EU as such. Moreover, social media communication is often heavily focused on visual content, which could also help explain the users' engagement (e.g., Farkas & Bene, 2021). Studies that only focus on textual elements thus might neglect one important aspect of communication on these platforms.…”
Section: Discussionmentioning
confidence: 99%
“…This also means that we cannot assess what the engagement with EU news, as operationalized in this study, might mean in terms of legitimacy or support for the EU as such. Moreover, social media communication is often heavily focused on visual content, which could also help explain the users' engagement (e.g., Farkas & Bene, 2021). Studies that only focus on textual elements thus might neglect one important aspect of communication on these platforms.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies on the use of social media in political communication in foreign literature. In a study dealing with Hungarian politicians, it was reported that the images used on Facebook and Instagram in political communication were generally used to personalize communication (Farkas & Bene, 2021), while in another study dealing with the use of social media by German political parties on Facebook, Twitter, Flickr and YouTube, social media was used a facilitating way for participation and democracy (Stieglitz, Brockmann, & Dang, 2012). In a study conducted in Nigeria on political advertising, it was concluded that the approach to political communication was moved to a negative dimension by making hate speech and fake reporting on social media (Oparaugo, 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Instagram strongly amplifies individual celebrities and influencers who visualize details of their personal lives for their followers (Cotter 2019;Farkas and Bene 2021). In a study of politicians' use of Instagram, Peng (2021) found that more personal and positive content tended to receive more engagement than staged, professional content.…”
Section: Framing and Communicating Climate Change On Social Mediamentioning
confidence: 99%
“…A main communication tool for Thunberg is Instagram, a social media platform centered around the user's ability to share visual content with accompanying textual captions (Farkas and Bene 2021). While Thunberg has amassed large social media audiences through each of her profiles, her largest audience is on Instagram with over 13 million followers 1 .…”
Section: Introductionmentioning
confidence: 99%